Evaluasi Peran Sekretariat Jenderal dalam Manajemen Supporting System guna Mendukung Tugas Konstitusional Anggota Dewan Perwakilan Daerah - Yulia Andriana (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This article examines the tension between the political needs of members of the Regional Representative Council of the Republic of Indonesia (DPD RI) and the bureaucratic system of the Secretariat General in managing the supporting system, particularly in the recruitment of support staff. As a non-partisan institution, the DPD relies on the individual strength of its members, while the Secretariat operates within a technocratic bureaucratic framework. Misalignment arises when the recruitment process is more influenced by political considerations than by meritocratic principles, creating a dilemma between political flexibility and bureaucratic accountability. This study employs a descriptive qualitative approach through document analysis. The findings indicate the need for structural reform and standardization of recruitment based on competence, transparency, and meritocracy. At the same time, there is a need to institutionalize political flexibility so that members can tailor support to their personal needs without compromising system accountability. By adopting modern human resource management theories, an adaptive and professional institutional design can establish an efficient and responsive supporting system that optimally supports the constitutional functions of the DPD RI.